COMMUNITY EMPOWERMENT MODEL OF THE SOCIAL TRANSFORMATION AND PUBLIC AWARENESS (STAPA) COMMUNITY FOR CHILD LABORERS IN TOBACCO PLANTATIONS FROM THE PERSPECTIVE OF COMMUNICATIVE ACTION - Abdur Rois (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
This paper describes the empowerment model as well as the process and practice of empowering the STAPA community for child labor in tobacco plantations in the perspective of communicative action, from community empowerment practices measured from community participation in empowerment program services from the STAPA community in terms of planning, program action, decision making to evaluation with communicative action practices. The focus of this research object is tobacco plantation child labor in Jember Regency. The purpose of this study is to analyze and describe the model of community empowerment from the perspective of communicative action, so from here the author's goal is to find a model of community empowerment in the practice of communicative action, therefore this study uses qualitative research methods, data collection methods are carried out by interviewing with the help of key informants, then the documentation method is collecting data from previous research and documentation from the government and the community. This study shows that the model of community empowerment in the perspective of communicative action that is practiced by the STAPA community is to use the concept of empowerment as an interjective communication as a stimulus for discourse in the target community so that the goal of community empowerment in tobacco plantation child workers can be achieved. Keywords: Model, Empowerment, STAPA, Labour, Child